Regional decline in growth rates of massive Porites corals in Southeast Asia. (29th July 2013) - Tanzil, Jani T.I.; Brown, Barbara E.; Dunne, Richard P.; Lee, Jen N.; Kaandorp, Jaap A.; Todd, Peter A.
Abstract This study reports the first well‐replicated analysis of continuous coral growth records from warmer water reefs (mean annual sea surface temperatures (SST) >28.5 °C) around the Thai–Malay Peninsula in Southeast Asia. Based on analyses of 70 colonies sampled from 15 reefs within six locations, region‐wide declines in coral calcification rate (ca. 18.6%), linear extension rate (ca. 15.4%) and skeletal bulk density (ca. 3.9%) were observed over a 31‐year period from 1980 to 2010. Decreases in calcification and linear extension rates were observed at five of the six locations and ranged from ca. 17.2–21.6% and ca. 11.4–19.6%, respectively, whereas decline in skeletal bulk density was a consequence of significant reductions at only two locations (ca. 6.9% and 10.7%). A significant link between region‐wide growth rates and average annual SST was found, and Porites spp. demonstrated a high thermal threshold of ca. 29.4 °C before calcification rates declined. Responses at individual locations within the region were more variable with links between SST and calcification rates being significant at only four locations. Rates of sea temperature warming at locations in the Andaman Sea (Indian Ocean) (ca. 1.3 °C per decade) were almost twice those in the South China Sea (Pacific Ocean) (ca. 0.7 °C per decade), but this was not reflected in the magnitude of calcification declines at corresponding locations. Considering that massive Porites spp. are major reef builders around Southeast Asia, this region‐wide growth decline is a cause for concern for future reef accretion rates and resilience. However, this study suggests that the future rates and patterns of change within the region are unlikely to be uniform or dependent solely on the rates of change in the thermal environment.